ALLISCO: pricing multiple joint products. Issue 4 (10th July 2015) - Singh, Gaganpreet; Pandey, Neeraj
Abstract : Subjectarea: Pricing, Marketing Management, Strategic Marketing, Strategic Management. Studylevel/applicability: The case can be used for a Pricing Course and Strategic Marketing, Marketing Management and Strategic Management courses delivered to post-graduate management programme (Master's level) students and/or for Management Development Programme's. Caseoverview: Alliance Intercontinental Sourcing Company LLP (ALLISCO) manufactured Steel Blanks for clutch plates used in two- and three-wheeler automobiles. Steel Blank plates further underwent a processing phase which included coating with leather cover to form the finished clutch plate. The primary raw material used by ALLISCO for its manufacturing process was sheet metal. The processing of the principal raw material resulted in the production of three joint products. The first joint product was "Steel Blank", the main product; the second joint product was "Inner Circle", which may be classified as a by-product; the third joint product was the left-over waste material and could be categorized as sheet scrap. The approximate increase in procurement cost of 8 per cent had considerably impacted the firm's profit margins. The dilemma that Rishabh Singla, Managing Partner, ALLISCO, now faced was how the increased differential could be distributed systematically among the three joint products. The challenge for ALLISCO was to preserve the percentage of gross profit margins by altering its existing pricing strategy. Expectedlearning outcomes: Understand the concept of multiple joint products; learn about choosing appropriate pricing strategies to price multiple joint products; comprehend how value-based pricing can extract untapped profits; and understand the importance of retaining gross profit margins (%). Supplementarymaterials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.